Risk Factor of COVID-19 Reinfection (Study on Patient at RSDC Wisma Atlet Kemayoran, Jakarta) (Universitas Aisyah Pringsewu (UAP) Lampung, 2022)
Background: Reinfection of COVID-19 is defined as a person who has recovered from infection with COVID-19 and then re-infected. The number of reports of reinfection events in several countries shows the magnitude of the problem of reinfection. Demographic factors, behavior, and medical history are risk factors for reinfection. Objective: To analyze the relationship between age, gender, history of comorbidities, use of public transportation, visiting public places, and behavior of using masks with the incidence of COVID-19 reinfection. Methods: This research is an analytic study with a cross-sectional approach. The subjects of this study were patients with a history of reinfection who met the inclusion and exclusion criteria from the epidemiological surveillance data at the Wisma Atlet Hospital, Jakarta in July – December 2021. Results: The incidence of reinfection with age 20-29 years (p=0.001) with POR 2.70 (95%CI 2.11-3.48), using public transportation (p=0.001) POR 1.80 (95%CI 1.45-2.21), and traveling to public places (p=0.001) POR 2.88 (95%CI 2.11-3.93). Variables that were not significant were gender (p=0.259) POR 1.13 (95%CI 0.92-1.38) and comorbid burden (p=0.193) POR 0.81 (95%CI 0.59-1.09). Conclusion: Age, use of public transportation, and traveling to public places contributed to the incidence of reinfection by 2.4, 1.4, and 2.0 times, respectively.